Digital Payment: Perspektif Gender dalam Pemilihan Jasa Pembayaran Digital - Aldilla Iradianty; Bayu Rima Aditya (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2021)
In today's digital era buyers and sellers are using digital payment applications with non-cash payment transactions, in this transaction, there are other parties involved, namely, digital payment providers, where the digital payment provider from the buyer will continue the transaction to the financial network used by the seller. quickly, safely and cheaply, and in real-time, so that immediately the buyer and seller know whether the transaction was successful or not because they are using their smartphone devices. Gender differences, between men and women, can lead to differences in terms of spending with transactions through digital payments, therefore this study will look at whether there are differences between men and women in terms of using digital payments. The research approach used is quantitative research with the help of a questionnaire. A total of 104 users were involved in this study to be asked for information about experiences in using various payments provided by four popular digital payment providers in Indonesia, namely Gopay, Ovo, LinkAja, and Dana. For data analysis, this study uses a different test analysis for each sample, and the results show that there is no difference in the use of digital payments seen from a gender perspective.